(untitled) (Innovative professional education, 2025)
Based on the goal-setting, tasks and main characteristics of Industry 5.0, the requirements for the organization of professional training of future specialists are disclosed. Based on the materials of the World Economic Forum «Future of Jobs 2025», a list of promising competencies that are most in demand in the labor market over the next five years is identified. Important areas for organizing professional and practical training of future skilled workers in the construction industry are identified.